Mitochondrial turnover and homeostasis in ageing and neurodegeneration. Issue 15 (1st June 2020) - Markaki, Maria; Tavernarakis, Nektarios
Abstract : Ageing is driven by the inexorable and stochastic accumulation of damage in biomolecules vital for proper cellular function. Although this process is fundamentally haphazard and uncontrollable, genetic and extrinsic factors influence senescent decline and ageing. Numerous gene mutations and treatments have been shown to extend the lifespan of organisms ranging from the unicellular Saccharomyces cerevisiae to primates. Most such interventions ultimately interface with cellular stress response mechanisms, suggesting that longevity is intimately related to the ability of the organism to counter both intrinsic stress and extrinsic stress. Mitochondria, the main energy hub of the cell, are highly dynamic organelles, playing essential roles in cell physiology. Mitochondrial function impinges on several signalling pathways modulating cellular metabolism, survival and healthspan. Maintenance of mitochondrial function and energy homeostasis requires both generation of new healthy mitochondria and elimination of the dysfunctional ones. Here, we survey the mechanisms regulating mitochondrial number in cells, with particular emphasis on neurons. We, further, discuss recent findings implicating perturbation of mitochondrial homeostasis in cellular senescence and organismal ageing as well as in age‐associated neurodegenerative diseases. Abstract :